Pengembangan Lembar Kerja Peserta Didik Muatan IPA SD - Vena Renata; Leo Charli; Asep Sukenda Egok (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the development and level of validity and practicality of Science Content Student Worksheets according to expert lecturers and practitioners, as well as to train students in learning activities to improve mastery of the material. This type of research is Research and Development with methods 1) analysis phase, 2) design, 3) development, 4) implementation, and 5) evaluation. Descriptive analysis of data, namely the results of the development of Science Content Student Worksheets material for changes in the form of objects consists of a general framework that contains cover pages, prefaces, table of contents, book instructions, basic competencies, and a content framework containing learning 1, learning 2, learning 5 IPA practice. as well as the final framework containing a bibliography, and conclusions. Based on data analysis, it can be concluded that the quality of the Science Content Student Worksheets developed is included in the very good category so that it is suitable for use with a percentage of 0.83% from linguists, 0.70% from media experts, and 0.97% from material experts. Meanwhile, the teacher's response obtained a percentage of 90% and student responses obtained a percentage of 93.33% with a very good category. Keywords: Science, Student Worksheets